2011
DOI: 10.4061/2011/925653
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Hemodynamic Sensors for Physiologic Cardiac Pacing in Heart Failure Patients

Abstract: The rate adaptive sensors applied to cardiac pacing should respond as promptly as the normal sinus node with an highly specific and sensitive detection of the need of increasing heart rate. Sensors operating alone may not provide optimal heart responsiveness: central venous pH sensing, variations in the oxygen content of mixed venous blood, QT interval, breathing rate and pulmonary minute ventilation monitored by thoracic impedance variations, activity sensors. Using sensors that have different attributes but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…The present study not only confirmed the ability of TBX18 to convert cardiomyocytes to iSANs in pigs but also comprehensively investigated the physiological relevance of such conversion. Ideal pacemakers, either biological or electronic, should respond to the complex interaction between autonomic regulation and physical activity (2, 25, 26). Until now, no study has comprehensively addressed this important limitation of biological pacemaker strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The present study not only confirmed the ability of TBX18 to convert cardiomyocytes to iSANs in pigs but also comprehensively investigated the physiological relevance of such conversion. Ideal pacemakers, either biological or electronic, should respond to the complex interaction between autonomic regulation and physical activity (2, 25, 26). Until now, no study has comprehensively addressed this important limitation of biological pacemaker strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Although AS is specifically designed to support physical activity associated with thoracic movement, CLS is not inferior for this kind of activity and is superior to AS during other forms of exercise, like cycling, mental exertion, or emotional stress [5][6][7][8][9][10]14]. In the randomized crossover PROVIDE study, twice as many chronotropically incompetent patients preferred CLS over AS [5].…”
Section: Discussionmentioning
confidence: 99%
“…In the CLS mode, the pacemaker couples the pacing rate to the myocardial contraction dynamics by measuring ventricular impedance variation [6][7][8]. As cardiac contractility is regulated by the autonomic nervous innervation, CLS is integrated into the natural cardiovascular control loop and responds to physical, mental, and emotional stress [5,[7][8][9][10].…”
Section: Pacemakermentioning
confidence: 99%
“…The first implantable cardiac pacemaker was designed to pace at a fixed rate without any attempt to mimic heart rate changes in physiology. Since then, pacemakers were introduced that adjusted the pacing rate by analyzing various sensor inputs and regulated the pacing rate accordingly . These rate adaption sensors include sensing changes in vibration, acceleration, and impedance.…”
Section: Commentarymentioning
confidence: 99%